2018
DOI: 10.3389/fimmu.2018.00100
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Biomarkers of Clinical Response to AHSCT in Autoimmunity

Abstract: Autoimmunity represents a broad category of diseases that involve a variety of organ targets and distinct autoantigens. For patients with autoimmune diseases who fail to respond to approved disease-modifying treatments, autologous hematopoietic stem cell transplantation (AHSCT) after high-dose immunosuppressive therapy provides an alternative strategy. Although more than 100 studies have been published on AHSCT efficacy in autoimmunity, the mechanisms that confer long-term disease remission as opposed to conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…Our results confirmed findings about general immune reconstitution dynamics observed in other settings, namely diverging kinetics among major subsets in which innate immunity typically precedes adaptive immunity 42 and the differentially affected T-cell subsets leading to an inverted CD4/CD8 ratio during the first year after transplantation. 7,10,29 Naive T-cell subsets were still below normal levels up to 1 year after aHSCT, whereas early circulating B cells were dominated by transitional and naive phenotypes, as shown before in the context of HSCT. 27 Because interaction between primed CD4 + T cells and naive B cells is essential for B-cell activation and differentiation, the delayed regeneration of the CD4 + compartment may be a key factor in slowing down the recovery of MBC subsets.…”
Section: Discussionsupporting
confidence: 73%
“…Our results confirmed findings about general immune reconstitution dynamics observed in other settings, namely diverging kinetics among major subsets in which innate immunity typically precedes adaptive immunity 42 and the differentially affected T-cell subsets leading to an inverted CD4/CD8 ratio during the first year after transplantation. 7,10,29 Naive T-cell subsets were still below normal levels up to 1 year after aHSCT, whereas early circulating B cells were dominated by transitional and naive phenotypes, as shown before in the context of HSCT. 27 Because interaction between primed CD4 + T cells and naive B cells is essential for B-cell activation and differentiation, the delayed regeneration of the CD4 + compartment may be a key factor in slowing down the recovery of MBC subsets.…”
Section: Discussionsupporting
confidence: 73%
“…Given that this association was not observed at month 12 after transplant, we did not expect to find an association between clinical outcome and diversification of the TCR repertoire in blood T cells at months 24 and 48 analyzed here. While none of our TCR repertoire analyses revealed associations with disparate long-term clinical outcomes, we accept the limitations of the study for identifying biomarkers of response as reported previously (13).…”
Section: Discussionmentioning
confidence: 53%
“…TCR repertoire diversity was analyzed using the Shannon entropy index in blood CD4 + and CD8 + T cells before therapy and at months 12, 24, and 48 after transplant. (B) Ratios of circulating CD4 + (top) and CD8 + (bottom) central memory (Tcm) and effector memory (Tem) to naive (Tn) cells were analyzed by flow cytometry, as previously reported (13). Filled triangles represent participants that met the primary endpoint for the HALT-MS study before month 60 after transplant, and open circles represent participants that stayed in remission from active MS until the last follow-up.…”
Section: Figure 5 CMV Infection After Ahsct Therapy Is Associated With Impaired Tcr Diversification and An Increased Ratio Of Memory-to-nmentioning
confidence: 99%
“…While defining public pathogenic T-cell clones in MS has to date proved elusive, a consistent pattern of immuno-ablation and immune reconstitution of T-cell populations following AHSCT has been established (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Following administration of an immuno-ablative conditioning regimen there is a bimodal recovery of T-cell populations.…”
Section: Introductionmentioning
confidence: 99%